去括号:-(2x^2-3x-1)=(2) 去括号:-2(1/6a^2-3a)=(3)化简:3(x-2)-2(1-2x)(4)化简求值:-2(x^2+1)+5(x+1)-0.5(4x^2-2x),其中x=-2

来源:学生作业帮助网 编辑:作业帮 时间:2024/07/29 14:17:40
去括号:-(2x^2-3x-1)=(2) 去括号:-2(1/6a^2-3a)=(3)化简:3(x-2)-2(1-2x)(4)化简求值:-2(x^2+1)+5(x+1)-0.5(4x^2-2x),其中x=-2
x){ڷY~OQEq-~OHY"HU"X1PӞi5停 NJ] 2ziY@ 5M5* F:O[=ٱV&HK87ÔRp;ȆzO?45ō@wi%ōa@ߘiTؚWZLPJVhBrY1X.^bl`X<7JF 1B4

去括号:-(2x^2-3x-1)=(2) 去括号:-2(1/6a^2-3a)=(3)化简:3(x-2)-2(1-2x)(4)化简求值:-2(x^2+1)+5(x+1)-0.5(4x^2-2x),其中x=-2
去括号:-(2x^2-3x-1)=
(2) 去括号:-2(1/6a^2-3a)=
(3)化简:3(x-2)-2(1-2x)
(4)化简求值:-2(x^2+1)+5(x+1)-0.5(4x^2-2x),其中x=-2

去括号:-(2x^2-3x-1)=(2) 去括号:-2(1/6a^2-3a)=(3)化简:3(x-2)-2(1-2x)(4)化简求值:-2(x^2+1)+5(x+1)-0.5(4x^2-2x),其中x=-2
1.原式=-2x^2+3x+1
2.原式=-1/3a^2+6a
3.原式=3x-6-2+4x=7x-8
4.原式=-2x^2-2+5x+5-2x^2+x=-4x^2+6x+3
把x=-2代进去得:-25